Capabilities of radiodiagnostic techniques for evaluating myocardial hemodynamics and contractility in ventricular arrhythmias - K. V. Zavadovskiy; V. V. Saushkin; Yu. B. Lishmanov (Вестник рентгенологии и радиологии)
As of now, the study of ventricular arrhythmias (VA) is of topical interest for modern arrhythmology and cardiology. These arrhythmias constitute about 30% of all the arrhythmias and have a diverse etiopathogenetic basis. Having no noticeableimpact on a patient’s quality of life, VA may cause ventricular fibrillation, severe circulatory disorders, and sudden cardiac death.Objective of this study – to compare the capabilities of radiation techniques for evaluating ventricular hemodynamics and contractility in patients with VA.A multitude of current radiodiagnostic methods, among which the most preferential technique cannot be set aside to reveal the causes of and to study hemodynamic disorders, is now used to evaluate ventricular hemodynamics and contractility in patientswith VA. Each procedure has its usage features in a contingent of patients with arrhythmias.